Linear programming technique for timber management planning in Peninsular Malaysia - Hadi, Yusuf (1987)
Linear Programming (LP) is introduced as a tool for timber management planning in Peninsular Malaysia. Timber management planning involves making decisions on which, when and how much forest area to harvest and subsequently to regenerate over a specified time period to ensure an acceptable log flow in the short term and a continuous log production and a continuous log production in the long term. An LP model is described which determines the number of ha of a forest management unit to be managed under a particular management regime such that an objective function is optimized, subject to constraints relating to size and accessibility of forest areas, periodic requirements and harvest and regulation policies. The model can incorporate several useful features such as variable planning-period lenghts, variable cutting cycles and several alternative objective functions and methods of controlling the harvest levels. These and other advantages of the LP technique are illustrated in an application of the model to plan timber supply from the forests of Peninsular Malaysia.